Aborto inseguro: determinantes sociais e iniquidades em saúde em uma população vulnerável – Favela Inajar de Souza, São Paulo, SP, Brasil - Fusco, Carmen Linda Brasiliense [UNIFESP] (2011)
Seventeen years after the International Conference on Population and Development (ICPD), Cairo, 1994, the situation of Unsafe Abortion (UA), considered a serious public health issue by the time the conference was held, remains the same in Brazil. Unsafe abortion is the main cause of maternal death in Latin America and the Caribbean, a region containing the highest unsafe, illegal and clandestine abortion rate. Approximately 21% of maternal deaths in the region occur due to complications related to unsafe abortion. This research took place on a peripheral community in the city of Sao Paulo: a cross-sectional study with the objective of estimating the prevalence of women that undergo unsafe abortions as well as identifying the social demographic characteristics (SDC) associated with it and its mortality rate. Interviews were conducted with women ranging from 15 to 54 years of age living in the community (Census). In the data analysis, after applying measures of association, univariate analyses of Multinomial Logistic Regression (MLR) were conducted for the IA (unsafe induced abortion) and SA (spontaneous abortion) categories having as a reference the NA (no abortion) category. The variables that resulted in associations with p<0.20 were selected for a Multiple MLR (MMLR) initial model for identifying the variables that would remain in the final model, with estimated Odds Ratio (CI=95% and p<0.05). In the results, the SDC whose variables remained in the final models of the MMLR analysis were: age at first sexual intercourse (< 16 years), gap (LB ≥ IN), number of sex partners (> 2), low schooling (< 4 years), ethnicity/color (black), marital status (not married) and acceptance of abortion due to insufficient economic conditions. From the results obtained, a study was developed in order to analyze the influence made by social determinants of health (SDH) on the occurrence of UA and associated SDC and the health inequities generated by them, whereas the main outcome in terms of health is unsafe abortion, along with its consequences and/or complications. This analysis discusses the SDC whose variables remain in the results, in addition to the per capita income and high morbidity rate, under an approach aimed at social determinants of health (SDH) according to the WHO concept and model and health inequities inflicted on the population. It was verified that UA and associated SDC are influenced by the described SDH, thus causing health inequities on several levels.